Methodological Reasoning Finds Law Using Normative Studies (Theory, Approach and Analysis of Legal Materials) - Rohman, Moh. Mujibur; Mu’minin, Nashrul; Masuwd, Mowafg; Elihami, Elihami (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2024)
Methodology is an important thing in research. A particular family of knowledge will experience development and is considered not rigid when studied using a certain methodology. Like water in the desert, scientific civilization will feel barren if it is not studied using the correct methodology. This article is a conceptual work on normative legal research which is studied normatively or doctrinally. The approach in this research uses a Conceptual Approach and an Analytical Approach. The author analyzes normative legal research methodology starting from naming to data analysis methods. The conclusions in this article were obtained in an inductive-deductive way. The research results show the importance of using methodology as a branch of knowledge construction. Normative research is the same as library research, only there are several approaches and analyzes that are not the same. It is hoped that legal researchers will not abandon the legal research methodology which has become a rule even though there are many perspectives.